Purification and characterization of thermostable beta-mannanase and alpha-galactosidase from Bacillus stearothermophilus. - Talbot, G (1990)
Bacillus stearothermophilus secretes beta-mannanase and alpha-galactosidase enzymatic activities capable of hydrolyzing galactomannan substrates. Expression of the hemicellulase activities in the presence of locust bean gum was sequential, with mannanase activity preceding expression of alpha-galactosidase activity. The hemicellulase activities were purified to homogeneity by a combination of ammonium sulfate fractionation, gel filtration, hydrophobic interaction chromatography, and ion-exchange and chromatofocusing techniques. The purified beta-D-mannanase is a dimeric enzyme (162 kilodaltons) composed of subunits having identical molecular weight (73,000). Maximal activity did not vary between pH 5.5 and 7.5. The beta-D-mannanase activity exhibited thermostability, retaining nearly full activity after incubation for 24 h at 70 degrees C and pH 6.5. The enzyme displayed high specificity for galactomannan substrates, with no-secondary xylanase or cellulase activity detected. Hydrolysis of locust bean gum yielded short oligosaccharides compatible with an endo mode of substrate depolymerization. Initial rate velocities of the mannanase activity displayed substrate inhibition and yielded estimates for Vmax and Km of 455 +/- 60 U/mg and 1.5 +/- 0.3 mg/ml, respectively, at 70 degrees C and pH 6.5. The alpha-galactosidase activity corresponded to a trimeric enzyme (247 kilodaltons) having subunits of identical molecular weight (82,000). The alpha-galactosidase had maximal activity at pH 7 to 7.5 and retained full activity after 24 h of incubation at 60 degrees C. The enzyme had only limited activity on galactomannan substrates as compared with hydrolysis of p-nitrophenyl alpha-D-galactose. Kinetics of p-nitrophenyl alpha-D-galactose hydrolysis yielded linear reciprocal plots corresponding to Vmax and Km of 195 +/- 10 U/mg and 0.25 +/- 0.02 mM, respectively, at 60 degrees C and pH 7. The characterization of the mannanase activity is consistent with its potential use in enzymatic bleaching of softwood pulps.